Analysis of the Dynamic Characteristic of Wind Turbine Planetary Gear System with Flexible Support - Jiang Gaige; Yin Yufeng; Si Shixiong; Gao Chongren (Jixie chuandong)
As the wind turbine gearbox mounted on a flexible support tower,the wind turbine tower will be bent and wiggled under the complex working conditions,and it will serious influence on the dynamic characteristic of the wind turbine gear transmission system. Considering the coupling effect of wind turbine tower swing and planetary wheel drive torsional vibration,by using the lumped parameter method,the dynamics analysis model of the flexible support of wind turbine planetary gear transmission system is established,and then the numerically solution is carried out with Matlab. By taking the instance analysis of the mainstream 1. 5MW wind turbine,the displacement progress of each part of planetary gear system under 16 seconds random time series wind load is got. The result shows that,in the process of wind turbine operation tower generates excessive vibration,and the vibration of the tower exacerbates the vibration of the components of wind turbine planetary gear system. Then,the impact of the flexible of the wind turbine tower must be considered in the wind turbine planetary gear design.